Evaluating Metacognitive Therapy to Improve Treatment of Anxiety and Depression in Cardiovascular Disease: The NIHR Funded PATHWAY Research Programme - Wells, Adrian; Reeves, David; Heal, Calvin; Davies, Linda M.; Shields, Gemma E.; Heagerty, Anthony; Fisher, Peter; Doherty, Patrick; Capobianco, Lora (Frontiers in Psychiatry, 2022)
Background: Anxiety and depression contribute to poorer physical and mental health outcomes in cardiac patients. Psychological treatments are not routinely offered in cardiac care and have mixed and small effects. We conducted a series of studies under the PATHWAY research programme aimed at understanding and improving mental health outcomes for patients undergoing cardiac rehabilitation (CR) through provision of metacognitive therapy (MCT). Methods: PATHWAY was a series of feasibility trials, single-blind, multicentre, randomised controlled trials (RCTs), qualitative, stated preferences for therapy and health economics studies. Findings: Patients felt their psychological needs were not met in CR and their narratives of distress could be parsimoniously explained by the metacognitive model. Patients reported they would prefer therapy over no therapy as part of CR, which included delivery by a cardiac professional. Two feasibility studies demonstrated that RCTs of group-based and self-help MCT were acceptable, could be embedded in CR services, and that RCTs of these interventions were feasible. A definitive RCT of group-MCT within CR (n=332) demonstrated significantly greater reductions in the severity of anxiety and depression, exceeding CR alone, with gains maintained at 12-month follow-up (SMD HADS total score = 0.52 at 4 months and 0.33 at 12 months). A definitive trial of self-help MCT is ongoing. Conclusion: There is a need to better meet the psychological needs of CR patients. Embedding MCT into CR demonstrated high acceptability and improved efficacy on psychological outcomes. Results support roll-out of MCT in CR with evaluation of national implementation. Registration: URL: NCT02420431; ISRCTN74643496; NCT03129282.